2004
DOI: 10.1097/01.psy.0000106907.24881.f2
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Depressive Mood on Relapse in Patients With Inflammatory Bowel Disease: A Prospective 18-Month Follow-Up Study

Abstract: Psychological factors such as a depressive mood associated with anxiety and impaired HRQOL may exert a negative influence on the course of IBD. Therefore, assessment and management of psychological distress should be included in clinical treatment of patients with IBD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

19
348
5
22

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 479 publications
(394 citation statements)
references
References 32 publications
19
348
5
22
Order By: Relevance
“…It has previously been shown that depressed mood can impact negatively on the course of inflammatory bowel disorder (IBD) (Mittermaier et al 2004). Patients with IBD and co-morbid depression have been found to require higher doses of steroids than those with IBD alone (Szigethy et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…It has previously been shown that depressed mood can impact negatively on the course of inflammatory bowel disorder (IBD) (Mittermaier et al 2004). Patients with IBD and co-morbid depression have been found to require higher doses of steroids than those with IBD alone (Szigethy et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Depression, anxiety and stress are related to low QoL in IBD patients, which affects the frequency of relapses and thus course of IBD [15,37]. However, one study found that depression and anxiety at baseline were not related to number of relapses over a 12 month period in IBD patients compared to controls [38].…”
Section: Mood Disordersmentioning
confidence: 99%
“…Thus these guidelines include the recommendation of screening patients with IBD for mental disorders and distress, to offer appropriate psychosocial care when needed, and to communicate with mental health specialists during this process. Furthermore, many authors recommend the use of psychotherapy in IBD patients with mood disorders [13,23,37]. Including psychosocial factors in the treatment of pediatric patients with IBD has also been recommended [35,46].…”
Section: Psychological Interventionsmentioning
confidence: 99%
“…심지어 증상이 완화되는 관해기 동안에도 재발에 대한 두려움으로 여전 히 삶의 활기나 활력이 저하되고 직장이나 사회생활에 어려움을 느끼고 있었다 (Graff, Walker, & Bernstein, 2009;Tanaka & Kazuma, 2005). 심리사회적 요인 중에는 우울 수준이 높을 때 삶의 질이 현저히 저하되었는데, 우울증상은 첫 발병 후부터 재발까지의 기간이 짧을 때 심했다 (Mittermaier et al, 2004). (Irvine, 2008).…”
unclassified
“…국외에서는 궤양성 대장염 환자의 우울이나 삶의 질을 파악 하고 (Lix et al, 2008;Mittermaier et al, 2004;Tanaka & Kazuma, 2005) 삶의 질에 영향을 미치는 요인을 다룬 연구 (Irvine, 2008;Van der Eijk et al, 2004) '심한 우울(severe depression)'로 분류하였다 (Beck et al, 1996). 도구의 신뢰도 Cronbach's ⍺값은 Kim 등 (2007) (Table 4).…”
unclassified